Bacterial nanocellulose with a shape-memory effect as potential drug delivery system - Mueller, Astrid; Zink, Matthias; Hessler, Nadine; Wesarg, Falko; Mueller, Frank A.; Kralisch, Dana; Fischer, Dagmar (RSC Advances, 2014)
In the steadily emerging field of applications for the natural biopolymer bacterial nanocellulose (BNC), the development of environmentally-friendly and cost-saving techniques to form xerogels by partial or complete dewatering is of great interest for convenient storage, handling and a reduced risk of microbial contamination. Air-dried BNC itself is not able to rehydrate after complete drying due to a structural collapse. In the present paper, it was supplemented with different hydrophilic, water-binding additives and characterized regarding morphology, re-swelling behavior, mechanical stability and potential as drug delivery system. A fast rehydration could be obtained by the addition of magnesium chloride > glucose > sucrose > sorbitol, with a maximum re-swelling percentage up to about 88% (magnesium chloride) of the initial wet weight. In contrast, poly(ethylene glycol) (8 kDa), lactose and trehalose reached only 12-30% whereas mannitol and sodium chloride only had a negligible effect. A high re-swelling value was found to be correlated with the preservation of the three-dimensional BNC network structure and mechanical characteristics such as compression and tensile strength. Confirming the relevance of these findings, the use of the hydrophilic model drug azorubine demonstrated the applicability of the shapememorized bacterial nanocellulose as drug delivery system with controllable release profiles.
CRIS-Team Scopus Importer:2020-10-13